Uji Aktivitas Antioksidan Ekstrak Etanol Daun Ranti (Solanum nigrum L.) dengan Metode DPPH - Sembiring, Mahral Effendi; Nainggolan, Tumpak V (Program Studi S1 Farmasi, STIKES Senior, Medan, 2024)
Ranti (Solanum nigrum L.) leaf is a solanaceae plant. This ranti leaf contains alkaloid, saponin, flavonoid and tannin compounds. Flavonoids in the human body function as antioxidants so it is very good for preventing anti-cancer diseases. This study aims to determine the antioxidant activity of ethanol extract of ranti leaves, Vitamin C and calculate the IC50 value of ethanol extract of ranti leaves and vitamin C using DPPH (1,1-diphenyl-2-picrylhydrazyl) method. The results of measuring antioxidant activity in the DPPH method showed that the ethanol extract of ranti leaves had very weak antioxidant activity with an IC50 value of 245.128 ppm, while the measurement results of vitamin C had very strong antioxidant activity with an IC50 value of 16.9235 ppm.